Alteration of serum and urinary bile acid sulfates in intrahepatic cholestasis - AMAKASU, Hitoshi; MIYAKAWA, Takatoshi; SUZUKI, Hiroshi; OTA, Shinichi; NAGAKURA, Takatomo; ISHII, Motoyasu; OTSUKI, Masao; GOTO, Yoshio (Kanzo, 1987)
Total sulfated bile acids of forty two serum samples and eleven urine samples from eight patients with acute intrahepatic cholestasis were analized with a newly established enzymatic fluorimetrical assay. As the degree of cholestasis advanced, the level of total serum sulfated bile acids elevated, but increasing rate of them gradually decreased. At the advanced stage of cholestasis, the proportion of total sulfated bile acids in total serum bile acids was significantly lower than that of healthy subjects. The level of total serum sulfated bile acids highly correlated with urinary excretion of sulfated bile acids. The renal clearance of sulfated bile acids was not altered during the course of cholestasis and the mean valule of them was 7.4±1.6ml per minutes. The production of sulfated bile acids was thought to be not increased in the advanced stage of cholestasis.